1972
DOI: 10.1128/aac.2.5.367
|View full text |Cite
|
Sign up to set email alerts
|

Silver Sulfadiazine: Effect on the Growth and Metabolism of Bacteria

Abstract: Even though the addition of silver sulfadiazine (AgSu) to purified deoxyribonucleic acid (DNA) results in the formation of AgSu-DNA complexes, no such complexes were detected in bacteria treated with AgSu. AgSu blocked macromolecular syntheses in treated bacteria, DNA synthesis being slightly more sensitive to this inhibitory action. The ribosomes, ribonucleic acid, and DNA isolated from treated cells were normal qualitatively. Bacteria deficient in DNA polymerase were not more sensitive than their parent stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 18 publications
3
45
0
Order By: Relevance
“…This, coupled with electrode corrosion would be used to explain any bacteriostatic action in other electrodes. The silver ion was suggested as the reason for such a strong bactericidal effect and other research on the antibacterial effects of silver sulfadiazine would appear to support this [45,46]. Electrically injected silver ions in this experiment were shown to be at least as effective as an antibiotic.…”
Section: Electrically Induced Bactericidal Effects Of Silvermentioning
confidence: 56%
“…This, coupled with electrode corrosion would be used to explain any bacteriostatic action in other electrodes. The silver ion was suggested as the reason for such a strong bactericidal effect and other research on the antibacterial effects of silver sulfadiazine would appear to support this [45,46]. Electrically injected silver ions in this experiment were shown to be at least as effective as an antibiotic.…”
Section: Electrically Induced Bactericidal Effects Of Silvermentioning
confidence: 56%
“…The activity of silver against multiresistant strains, including methicillin sodium-resistant staphylococci and vancomycin-resistant enterococci is particularly important. This action is postulated to be mediated by binding of the silver ions to cellular DNA [28] and the cell membrane [29]. Resistance to silver has been reported in a small number of organisms, including some strains of Proteus mirabilis, Enterobacter cloacae, Citrobacter freundii, and Klebsiella pneumoniae [30].…”
Section: Discussionmentioning
confidence: 99%
“…Sulphadiazine potentiates the action of AgSD and it has been suggested that this may be due to a reduced degree of ionisation of the AgSD, thus slowing the release of Ag into the medium [18]. Although AgSD interacts irreversibly with DNA to form a complex in vitro [23], this does not appear to be its mode of action in vivo and Ag 2 ion is the active agent [24]. Silver ions react with DNA in vitro, Âźrstly in a weak interaction then strongly with the silver ions becoming incorporated by bonding between the base pairs [25].…”
Section: Introductionmentioning
confidence: 99%
“…Silver ions react with DNA in vitro, Âźrstly in a weak interaction then strongly with the silver ions becoming incorporated by bonding between the base pairs [25]. Although it has been suggested that binding to DNA is the mode of action in vivo [18], other workers suggest that Ag 2 binds preferentially to external cell structures and that only small amounts are bound to DNA [24]. Cells of S. aureus treated with AgSD were enlarged, some retraction of the cytoplasmic membrane from the cell wall was seen and division planes between bacteria became indistinct, supporting the view that the effect is on external cell structures [26].…”
Section: Introductionmentioning
confidence: 99%